John Fowles (St. Martin's Press, 1998)
In this book, James Acheson traces the development of Fowles's fiction from The Collector, The Magus and The French Lieutenant's Woman through to The Ebony Tower, Daniel Martin and A Maggot. He shows how the sexual element in Fowles's early novels - up to and including The French Lieutenant's Woman - is interwoven with the author's interest in existentialism. In each of the early works, the main characters are obliged to struggle not only with sexual issues but to choose between a life of humdrum conventionality on the one hand, and the painful discovery of their own 'authenticity' on the other. By the 1970s, however, Fowles's interest in existentialism had begun to wane, his disillusionment taking varying forms in his collection of short stories. The Ebony Tower, and in the two novels that followed it, Daniel Martin and A Maggot.